Three-dimensional imaging of magnetic nanoparticles using multiple pickup coils and field-free line. (17th January 2018) - Muta, Masahiro; Hamanaga, Shohei; Tanaka, Naoki; Sasayama, Teruyoshi; Yoshida, Takashi; Enpuku, Keiji
Abstract: We performed three-dimensional detection of magnetic nanoparticle (MNP) samples using third-harmonic signal detection. In this method, a combination of five pickup coils and a gradient field with a field-free line was used to acquire three-dimensional MNP sample position information. The resulting two-dimensional maps of the signal fields generated by the MNP samples are sufficient for three-dimensional MNP image reconstruction. In the experiments, two MNP samples with different Fe contents were set at different positions. Two-dimensional field maps were measured using the five pickup coils, and the three-dimensional MNP sample distribution was then reconstructed from these field maps by solving an inversion problem. We demonstrated three-dimensional detection of two MNP samples where we reconstructed the three-dimensional positions and the Fe contents of these two MNP samples with reasonable accuracy. These results indicate the feasibility of the proposed system for three-dimensional magnetic particle imaging.